The Matrix of Human Resources Development Factors in Small and Medium Enterprises Typical Regional Products in Palembang - Trihandayani, Zaleha (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2018)
All this time, the typical regional product employees in Palembang were only directed to be able to work from skills that were owned informally and were handed down from generation to generation so that the ability to work for their employees was still simple or traditional, even though a small portion had penetrated into international markets, such as songket which was in demand in allied countries, for example: Malaysia and Brunei Darussalam. Pempek dan kerupuk kemplang that had been sold in neighboring countries, while carving cabinets had not entered the international market. The factor matrix of human resource development in small and medium enterprises typical regional products in Palembang aimed to improve the knowledge, skills, and emotional intelligence of employees of small and medium businesses typical regional products in Palembang. For example: kerupuk kemplang from Taiwanese were superior in the international market than kerupuk kemplang from palembang, it was expected that the typical regional products in Palembang would still not be left behind despite having entered various similar products from outside the region and even outside the country. The research design used in conclusive design that was specifically descriptive with purposive sampling method. It was expected that the typical regional products in Palembang could continue to survive and even be able to compete with similar products from domestic and abroad. This research was part of a dissertation of intellectual intelligence, emotional intelligence and employee empowerment of job satisfaction and loyalty employees of small and medium enterprises typical regional products in Palembang. The continuation of this dissertation was a research model of the strategy of challenging human resources in small and medium enterprises typical regional products in Palembang.